1999
DOI: 10.1080/016502599383928
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-home Child Care Research: A Cultural Perspective

Abstract: This paper analyses the cultural context of inquiry and research into the effects of out-of-home child care on children’s development. In particular, it attempts to show how the study of such child care has been shaped by a Western world view in which white, middle class values and social ideology are particularly salient. The effects of this cultural context can be seen in the basic assumptions of studies on out-of-home child care, in the questions these studies pose for investigation, and in the motivation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 80 publications
1
25
0
7
Order By: Relevance
“…Similarly, parents were more likely to report using cooperative feeding practices when they were from Caucasian backgrounds, were married, or were college educated. These findings align with previous research that has found responsive, individualized care to be highly valued among white, middle-class and higher income caregivers (Rosenthal, 1999). The project also reinforced findings from previous studies with older children that demonstrated that one's parenting style (i.e., Authoritarian, Authoritative, or Permissive) or child-rearing beliefs tend to mirror the control and responsiveness exerted during mealtime interactions with young children.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Similarly, parents were more likely to report using cooperative feeding practices when they were from Caucasian backgrounds, were married, or were college educated. These findings align with previous research that has found responsive, individualized care to be highly valued among white, middle-class and higher income caregivers (Rosenthal, 1999). The project also reinforced findings from previous studies with older children that demonstrated that one's parenting style (i.e., Authoritarian, Authoritative, or Permissive) or child-rearing beliefs tend to mirror the control and responsiveness exerted during mealtime interactions with young children.…”
Section: Discussionsupporting
confidence: 80%
“…As Rosenthal (1999) has noted, the guidelines for "quality care" in the United States are heavily rooted in white, middle class values and social ideological goals and may not always align well with the goals and practices of the families who have children in care. For example, in Western societies where individual achievement and expression tend to be valued, adults' sensitivity and responsiveness to children's individual needs are widely accepted as important aspects of caregiving.…”
mentioning
confidence: 99%
“…In terms of child-rearing beliefs, preschool teachers' views were more congruent with those of nonmigrant mothers than they were with migrant mothers. Additionally, it shows that the preschool teachers tend to promote socialization goals in conformity with Western child care philosophy, as described by Rosenthal (1999). It would be desirable to implement a wider spectrum of cultural orientations in early child care to address multiple child-rearing beliefs and to reduce the dominance of a single cultural orientation.…”
Section: Resultsmentioning
confidence: 95%
“…Some studies have found differences between Blacks and Hispanics, and Anglos and Hispanics (Kazak & Nachman, 1991). Culture, although not studied systematically, has been seen as an important consideration in morbidity and mortality rates as well as compliance with cancer, treatments/ prognoses, and so on (Johnson, 1998;Pask, 1997;Rosenthal, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%